(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dental caries is an irreversible microbial disease of the calcified tissues of the teeth. It is a bacterial driven, generally chronic, site-specific, the multifunctional dynamic disease process that results when the PH drop results in net mineral loss over time. It is one of the most prevalent diseases affecting mankind. Cariogenic bacteria enter the dental biofilm early in life and subsequently invade the host tissue during favourable environment condition, to cause the disease. Many studies and researches show that this disease process can be interrupted. This article will give a clear idea of the method by which the host defence system can be aroused to combat dental caries caused by the crucial antigen related to Streptococcus mutans. Analyzing the fact that more effective public dental health care measures are needed to combat this dental caries, this article critically evaluates the recent signs of progress in the development of mucosal adjuvants, delivery systems for the dental vaccine, and also limitations of caries immunization.